Peranan Relawan Pajak dalam Pendampngan Pelaporan SPT Tahunan Orang Pribadi Melalui E-Filing di KPP Pratama Palembang Seberang Ulu - Putri Erika Syahrani; Citra Indah Merina (Masyarakat Ekonomi Syariah Bogor, 2025)
Taxes are one of the main sources of revenue used for national development in implementing various public programs and services. The Directorate General of Taxes (DJP) has developed a digital tax reporting system called E-Filing as an effort to increase taxpayer compliance. E-Filing was created to simplify tax activities for both individual and corporate taxpayers. However, many taxpayers still face difficulties in using the digital system. Therefore, the DJP has collaborated with universities in Indonesia to create a program called Tax Volunteers. This program involves students in assisting taxpayers with the aim of providing tax education and increasing taxpayer compliance. This study aims to describe the role of tax volunteers in assisting with the submission of annual tax returns for individuals through E-Filing at the KPP Pratama Palembang Seberang Ulu . This study uses a qualitative descriptive approach with data collection through observation and interviews. The results of this study indicate that tax volunteers play a crucial role in assisting taxpayers by providing education and technical assistance, thereby accelerating the reporting process and enhancing taxpayers' awareness and compliance regarding taxation, particularly annual tax returns.